Structure of B77 sarcoma virus RNA: stabilization of RNA after packaging. - Stoltzfus, C M (1975)
Extracellular maturation of Bratislava 77(B77) sarcoma virus RNA involves a stabilization of linkage between 35S subunits since the Tm of 60 to 70S RNA in the presence of 0.5 M NaCl increases from 56 to 67.5 C as the age of the virus increases. This stabilization process is strongly temperature dependent; the rate at 45 C is increased fourfold over the rate at 37 C. As a result of the instability of the immature RNA, denaturation to subunits occurs at room temperature during phenol extraction. This dissociation can be prevented by increasing the NaCl concentration during the extraction. The data support a model which proposes that RNA subunits of oncornaviruses exist as assembled 60 to 70S RNA even in immature virions but that the linkages between subunits are stabilized as a function of time. These linkages appear to be maintained by nucleotide base pairing rather than by protein. However, isolated RNA does not undergo stabilization, suggesting that some other component of the virion is necessary for the process to occur.